Sistem Monitoring Pertanian Cerdas dan Irigasi Otomatis Berbasis Teknologi Internet of Things (IoT) - Yogi Priyo Istiyono; Siti Rokhmanila; Ojak Abdul Rozak (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2026)
Efficient irrigation management and real-time environmental monitoring are crucial for improving agricultural productivity and optimizing water use, especially in small-scale and urban farming systems. This study presents the development and experimental evaluation of an Internet of Things (IoT)-based environmental monitoring and automated irrigation system for agricultural applications. The system integrates a NodeMCU ESP8266 microcontroller with capacitive soil moisture, soil pH, and DHT11 temperature sensors to monitor key environmental parameters. Data are transmitted via Wi-Fi to the Blynk cloud platform, enabling real-time monitoring through a smartphone interface and a 16×2 LCD display. Automated irrigation is implemented using a relay-controlled 5V DC water pump that operates based on predefined soil moisture thresholds. Experimental validation was conducted by comparing sensor measurements with a standard reference instrument (ETP-302). The results indicate average errors of 3.4% for soil moisture, 4.1% for soil pH, and 2.8% for temperature measurements. The irrigation system successfully activated within the dry soil threshold range (430–520 ADC) and stopped automatically when sufficient moisture was reached, reducing unnecessary water consumption. Overall, the proposed low-cost IoT-based system demonstrates reliable performance, acceptable accuracy, and effective irrigation control, supporting smart agriculture and sustainable precision water management.